(untitled) (Journal of Forensic Medicine & Toxicology, 2020)
The term “complex suicide” refers to suicides in which more than one suicide method is applied. In planned complex suicides, two or more methods are employed simultaneously to ensure that death will occur even if one method fails. In unplanned complex suicides, several other methods of suicide are tried after the first method fails or when the chosen method is unbearably painful that it cannot be carried out to completion. In our case, a 27- year old male was brought to casualty with a history of consumption of rat killer poison combined with self immolation. After two days of treatment, he succumbed to death. Autopsy findings revealed 45% - 50% of superficial to deep burns on the upper part of the body and viscera analysis was positive for zinc phosphide compound. The events, in this case, that is self-immolation and rat killer poisoning were sufficient individually to cause death. To the best of our knowledge, the combination of methods used in this case is unique.